PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN IKLIM ORGANISASI TERHADAP KINERJA GURU SMP NEGERI 1 PARENGAN TUBAN - Abid Failusuf Hasan; C. Sri Hartati; Mei Indrawati (MAP (Jurnal Manajemen dan Administrasi Publik), 2018)
This study aims to determine the leadership of school principals, climatic organizations and teacher performance in SMP Negeri 1 Parengan Tuban. In addition to know and analyze the leadership and performance of teachers also partially affect the performance of teachers SMP Negeri 1 Parengan Tuban. The population in this study were all teachers of SMP Negeri 1 Parengan Tuban which locked 47 people. The sample in this study was teachers of SMP Negeri 1 Parengan Tuban which totaled sampling or using sampling census method. The number of samples of this study as many as 47 people hereinafter referred to as respondents. In this research, simple linear regression analysis technique. The result of the analysis shows that there is a significant influence between principal performance and organizational climate on teacher performance in SMP Negeri 1 Parengan Tuban. There is a significant role between principal and climate leadership simultaneously on the performance of teachers of SMP Negeri 1 Parengan Tuban. Keywords: principal leadership, organizational climate, teacher performance